The generation of community social capital in the Poble Sec community plan (Barcelona). Issue 4 (8th August 2022) - Martínez, Lucas M.; Úcar, Xavier
ABSTRACT: The perspective of social capital has gained prominence in the last 25 years in research and intervention in the social and educational fields.There is an open debate on the application of this concept in community action processes. The objective of this article is to identify and analyze the basic factors that influence the generation of social capital within the Community Development Plan of Poble Sec de Barcelona.A qualitative research process was designed in two phases: one to review the existing academic literature on the factors that generate community social capital, and a second focused on the case analysis of a Community Development Plan.Results such as the wealth of community associations, the feeling of belonging and the ability to mobilize neighbors to get involved in collective actions of a social nature, show that Community Development Plans can provide an adequate context for the generation of social capital.